Effects of damming on the distribution and methylation of mercury in Wujiang River, Southwest China. (October 2017) - Zhao, Lei; Guo, Yanna; Meng, Bo; Yao, Heng; Feng, Xinbin
Abstract: Newly built reservoirs are regarded as sensitive ecosystem for mercury (Hg) methylation. A comprehensive study was conducted to understand the influence of damming on the distribution and methylation of Hg within a river-reservoir ecosystem in Wujiang River Basin (WRB), Southwest China. Hg species in inflow-outflow rivers of six cascade reservoirs were analyzed each month during 2006. Mean concentrations of total Hg (THg) and methylmercury (MeHg) in river water in WRB were 3.41 ± 1.98 ng L −1 and 0.15 ± 0.06 ng L −1, respectively. THg and particulate Hg (PHg) concentrations in outflow rivers of reservoirs significantly decreased after dam construction, suggesting that a considerable amount of PHg was intercepted by way of sedimentation. However, the influence of damming on the distributions of dissolved Hg (DHg) and reactive Hg (RHg) in rivers was less pronounced. MeHg concentrations in outflow rivers of the older reservoirs significantly increased compared to inflow rivers with the maximum increasing factor of 92%, indicating the active net Hg methylation in the reservoirs. However, the difference between MeHg in inflow rivers and outflow rivers were less pronounced in the newly constructed reservoirs, indicating that these reservoirs were not active sites of Hg methylation. The construction of the cascade reservoirs resulted in the elevation of MeHg in several sections of the Wujiang River, which attributed to the net Hg methylation in reservoirs and discharge of MeHg from hypolimnion. MeHg-enriched water in outflow rivers from hypolimnetic water could be transported to downstream, posing potential threat to the aquatic food web and human health. Highlights: Total Hg concentrations decreased from upstream to downstream of the Wujiangriver as the result of the intercepted particulate Hg. Net Hg methylation and the output of MeHgfrom reservoirs increased with progressive increase of trophic stage in reservoir. Net Hg methylation and discharge of MeHgfrom hypolimnion resulted in the elevation of MeHgin several sections of the river.